CONTEMPORARY NEEDS OF MEDIA LEARNING MATERIALS FOR FUTURE Z-ENGINEERS - Veide, Zoja; Strozheva, Veronika (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Modern students are digital natives: from an early age, they are used the Internet, social networks and mobile systems. Due to the specific brain structure of Generation Z students, the use of traditional teaching tools makes the learning process not effective. Also, an insufficient number of lecture hours in curricula requires from students more independent work. This article presents the experience of creating interactive teaching materials designed to study and master the skills of graphical engineering subjects. Educators of technical universities from five countries took part in the development of the material. These interactive teaching tools are created with the aim of improving the quality of engineering education, the rapid and effective presentation of educational material, which will contribute to the understanding of difficult topics.